Plant Cell Wall-Like Soft Materials: Micro- and Nanoengineering, Properties, and Applications - Koshani, Roya; Pitcher, Mica L.; Yu, Jingyi; Mahajan, Christine L.; Kim, Seong H.; Sheikhi, Amir (Nano-Micro Letters, 2025)
Plant cell wall (CW)-like soft materials, referred to as artificial CWs, are composites of assembled polymers containing micro-/nanoparticles or fibers/fibrils that are designed to mimic the composition, structure, and mechanics of plant CWs. CW-like materials have recently emerged to test hypotheses pertaining to the intricate structure–property relationships of native plant CWs or to fabricate functional materials. Here, research on plant CWs and CW-like materials is reviewed by distilling key studies on biomimetic composites primarily composed of plant polysaccharides, including cellulose, pectin, and hemicellulose, as well as organic polymers like lignin. Micro- and nanofabrication of plant CW-like composites, characterization techniques, and in silico studies are reviewed, with a brief overview of current and potential applications. Micro-/nanofabrication approaches include bacterial growth and impregnation, layer-by-layer assembly, film casting, 3-dimensional templating microcapsules, and particle coating. Various characterization techniques are necessary for the comprehensive mechanical, chemical, morphological, and structural analyses of plant CWs and CW-like materials. CW-like materials demonstrate versatility in real-life applications, including biomass conversion, pulp and paper, food science, construction, catalysis, and reaction engineering. This review seeks to facilitate the rational design and thorough characterization of plant CW-mimetic materials, with the goal of advancing the development of innovative soft materials and elucidating the complex structure–property relationships inherent in native CWs. Highlights: 1 This review provides a detailed account of engineered plant cell wall (CW)-mimetic soft materials, which are designed to replicate the intricate composition, structure, and mechanical properties of natural plant CWs. 2 Experimental methods to create CW-like materials are reviewed, and relevant characterization techniques, including mechanical, chemical, structural, and morphological analyses, are discussed. 3 The applications of CW-like materials in several fields, including food packaging, edible films, drug delivery, construction materials, and biocatalysis are highlighted.